2007
DOI: 10.1007/s00280-007-0630-5
|View full text |Cite
|
Sign up to set email alerts
|

Two peptides derived from ras-p21 induce either phenotypic reversion or tumor cell necrosis of ras-transformed human cancer cells

Abstract: We conclude that these peptides block tumor but not normal cell growth likely by blocking oncogenic ras-p21-induced phosphorylation of JNK, an essential step on the oncogenic ras-p21-protein pathway. These peptides are therefore promising as possible anti-tumor agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The same authors point out that the region comprised between amino acids 55 and 71 of Ras make also contact with GAP and SOS proteins. Pincus and co-workers affirm that their peptides PCN-7 (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) and PCN-2 (96-110) block interaction with Raf and have an anti-tumor effect on cell lines. They also affirm that both peptides induce phenotypic reversion of the HT-1080 cell line to non-transformed cells but cause tumor cell necrosis on MIA-PaCa2 cell line.…”
Section: Raf-binding Assays On Cellulose-bound Peptides Containing Ras Sequencesmentioning
confidence: 98%
See 1 more Smart Citation
“…The same authors point out that the region comprised between amino acids 55 and 71 of Ras make also contact with GAP and SOS proteins. Pincus and co-workers affirm that their peptides PCN-7 (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) and PCN-2 (96-110) block interaction with Raf and have an anti-tumor effect on cell lines. They also affirm that both peptides induce phenotypic reversion of the HT-1080 cell line to non-transformed cells but cause tumor cell necrosis on MIA-PaCa2 cell line.…”
Section: Raf-binding Assays On Cellulose-bound Peptides Containing Ras Sequencesmentioning
confidence: 98%
“…They speculate that PCN-2 might block oncogenic Ras by inhibiting its interaction with JNK. PCN-7 could block the interaction of oncogenic Ras with Raf [38,39]. They suggest that both oncogenic and wild type Ras requires Raf activation, and assume, without demonstration, that each Ras protein interacts with Raf in different ways, resulting in differential activation of downstream kinases.…”
Section: Raf-binding Assays On Cellulose-bound Peptides Containing Ras Sequencesmentioning
confidence: 99%
“…Kanovsky et al [108] found that two ras-p21 peptides PNC-7 and PNC-2 (96–110 residues) induced phenotypic reversion of both ras-transformed rat pancreatic cancer cells (TUC-3) to their untransformed phenotypes. These peptides were linked to penetratin a CPP; which induced the phenotypic reversion of ras-transformed human fibrosarcoma cells (HT-1080) to its untransformed phenotype [109]. Both peptides induced the death of MIA-PaCa-2 human pancreatic cancer cells by inhibiting ras-p21 phosphorylation [109], however it did not cause these cells to undergo phenotypic reversion.…”
Section: Therapeutic Peptides Target Signal Transduction Pathwaysmentioning
confidence: 99%
“…These peptides were linked to penetratin a CPP; which induced the phenotypic reversion of ras-transformed human fibrosarcoma cells (HT-1080) to its untransformed phenotype [109]. Both peptides induced the death of MIA-PaCa-2 human pancreatic cancer cells by inhibiting ras-p21 phosphorylation [109], however it did not cause these cells to undergo phenotypic reversion.…”
Section: Therapeutic Peptides Target Signal Transduction Pathwaysmentioning
confidence: 99%
“…Therapeutic peptides have been designed to inhibit MAPK pathways. Two ras-p21 peptides, (PNC-7 and PNC-2, both derived from Ras gene encoded 21 protein), were conjugated with the CCP penetratin to block oncogenic ras-p21, inducing the phenotypic reversion of ras-transformed human fibrosarcoma cells (HT-1080) to the untransformed phenotype . In another example, c-Jun amino terminal kinase (JNK) peptide inhibitors, derived from the JNK interacting protein (JIP), were conjugated to CCPs ( e.g.…”
Section: Peptide Therapeutics In Cancer Therapymentioning
confidence: 99%